Estimation of paracetamol in urine to assess the diurnal variation - Bhowmik, Mithun Chandro; Misbahuddin, Mir; Bhuiyan, Habiba Akhter (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The aim of the present study was to evaluate the diurnal variation of the pharmacokinetics of paracetamol by estimating the urinary free paracetamol level after single oral administration of paracetamol (500 mg) tablet to 24 healthy male volunteers (students of a Medical College). The volunteers were given paracetamol tablet at 0800, 1400 and 2000 hours in three different days (two weeks apart) and the urine samples of the volunteers were collected at just before and four hours after paracetamol administration. The samples were analyzed for free paracetamol using HPLC. The mean age was 21.1 ± 1.3 years and the body weight was 63.9 ± 10.9 kg. Three peaks were detected in the HPLC and one of them was identified for free paracetamol (RT= 4.7 min). The urine volume was nearly similar in all three times. After administration at 0800 hour, total free paracetamol excretion was significantly more than at 1400 and 2000 hours (p<0.001). The present study indicates that the dose reduction of paracetamol is required at morning than the afternoon or evening dose.